2002
DOI: 10.1097/00001199-200210000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Computer-based Neuropsychological Assessment

Abstract: Objectives: To present current applications of computer-based neuropsychological assessment, including the assessment of sports-related concussion, symptom validity testing, and the remote administration of tests through the Internet. Problem areas: If computer-based assessment benefits are to become popularized, a few issues will need to be addressed: the development of psychometric data based on comparisons with long-standing empirically sound test measures; additional validation of measures by parties not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(101 citation statements)
references
References 83 publications
1
94
0
6
Order By: Relevance
“…Even where test developers refer to such stimuli as "verbal" or "verbally-based," or such subtests as "verbal memory," computer-based measures cannot assess efferent language or verbal modalities. (For a more comprehensive review of computer-based assessment, see Schatz & Browndyke, 2002). The literature is not entirely in agreement with respect to the psychometric equivalence of computerized versus paper-based assessment measures.…”
mentioning
confidence: 99%
“…Even where test developers refer to such stimuli as "verbal" or "verbally-based," or such subtests as "verbal memory," computer-based measures cannot assess efferent language or verbal modalities. (For a more comprehensive review of computer-based assessment, see Schatz & Browndyke, 2002). The literature is not entirely in agreement with respect to the psychometric equivalence of computerized versus paper-based assessment measures.…”
mentioning
confidence: 99%
“…The findings of this study support their conclusions, speaking in favor of the use of computer-based tests in the neuropsychological assessment of executive functions. A similar assumption is defended by Schatz and Browndyke (2002), who believe that computer-based tests can offer benefits over paperand-pencil evaluations of cognitive functions during neuropsychological assessment.…”
Section: Resultsmentioning
confidence: 82%
“…Computers have been used in neuropsychology with increasing frequency for many years because of the many advantages that go beyond administration simplicity and data collection [67][68][69]. As Woo [67] and Collerton et al [70] have shown, computers can improve neuropsychological assessment in several ways: 1) Computers provide precise measurements at the millisecond level, providing a more sensitive measure of cognitive impairment, especially in high-functioning older adults and in patients with milder levels of cognitive deficit.…”
Section: Neuropsychological Assessment In Simulated Environmentsmentioning
confidence: 99%